The Boma: Drought insurance - Breaking the cycle of loss for millions of pastoralists - International Livestock Research Institute (International Livestock Research Institute, 2022)
Droughts have always occurred in the Horn of Africa, but in the past few years they have begun happening much more frequently. An award-winning scheme of index-based livestock insurance could provide a lifeline for millions of pastoralists whose livelihoods are affected by drought. There is no need to wait for a drought to become severe, for animals to die, or people to starve. Instead this scheme can help resilent pastoralists deal with climate shocks before they happen. Presenters Brenda Coromina and Elliot Carleton take a look at how the insurance works, and why it is needed. The index-based livestock insurance project at ILRI is run with the help of a variety of partners, including the World Bank, Cornell University, UC Davis, and the Kenyan government. This episode features a clip from a video interview with Guyo Malicha Roba by The Elephant.